IMPACTOS SOCIOCULTURALES GENERADOS POR LAS ACTIVIDADES TURISTICAS EN EL CANTÓN VALENCIA, 2022 - Espinoza Aguirre, Erika Mayerly (2022)
Tourism is a recreational activity that consists of visiting a place or several that are outside the usual environment of a person, these can be for work, pleasure or others, which can result in various positive and negative impacts at the time of travel. that people move from one place to another. The sociocultural impacts arise as a cause of the interaction that exists between a tourist and a resident, resulting in several changes being generated in a specific place as consequences of the interaction that exists between several people, these changes can be positive or negative in the sociocultural field. To carry out this research project, the different perceptions of the inhabitants about the effects of tourism that is practiced in this place were analyzed, in addition an exploratory study was carried out with 382 native people of the canton in which the research scale was used. Likert type, where respondents were allowed to express their perception about the different impacts generated by tourism activities. The results of this research indicate that the sociocultural impacts that have been generated by tourist activities in this place are mostly positive, that is, tourism has reinforced the image of Valencia as a canton worth visiting and being promoted touristically.